Pengaruh Kualitas Sumber Daya Manusia dan Disiplin Kerja Terhadap Kinerja Tenaga Harian Lepas di Biro Pengadaan Barang dan Jasa Skretariat Daerah Provinsi Sulawesi Utara - Angel Gloria Mokorowu; Joyce Rares; Salmin Dengo (Sam Ratulangi University, 2023)
ABSRACT This study aims to determine the effect of the quality of human resources and work discipline on the performance of freelance workers at the Bureau of Procurement of Goods and Services of the Regional Secretariat of North Sulawesi Province. This research uses a census research type with a quantitative approach. The population and sample in this study were all freelance daily workers, totaling 42 people. The collection of research data comes from questionnaires, observation and literature studies with data analysis techniques is multiple regression analysis. Based on the results of the study, it shows that the quality of human resources and work discipline have an influence on the performance of freelance workers. The percentage of the independent variable to the dependent variable has a coefficient of determination of 0.644. These results show that the ups and downs of the performance of freelance workers at the Bureau of Procurement of Goods and Services for the Regional Secretariat of North Sulawesi Province are influenced by the quality of human resources and work discipline of 64.4%, while the remaining 35.6% influenced by other factors not examined in this study. Keywords: Quality of Human Resources, Work Discipline, Performance.